Global Impact of Oncogenic Src on a Phosphotyrosine Proteome - Luo, Weifeng (2008)
Elevated activity of Src, the first characterized protein-tyrosine kinase, is associated with progression of many human cancers, and Src has attracted interest as a therapeutic target. Src is known to act in various receptor signaling systems to impact cell behavior, yet it remains likely that the spectrum of Src protein substrates relevant to cancer is incompletely understood. To better understand the cellular impact of deregulated Src kinase activity, we extensively applied a mass spectrometry shotgun phosphotyrosine (pTyr) proteomics strategy to obtain global pTyr profiles of Src-transformed mouse fibroblasts as well as their nontransformed counterparts. A total of 867 peptides representing 563 distinct pTyr sites on 374 different proteins were identified from the Src-transformed cells, while 514 peptides representing 275 pTyr sites on 167 proteins were identified from nontransformed cells. Distinct characteristics of the two profiles were revealed by spectral counting, indicative of pTyr site relative abundance, and by complementary quantitative analysis using stable isotope labeling with amino acids in cell culture (SILAC). While both pTyr profiles are replete with sites on signaling and adhesion/cytoskeletal regulatory proteins, the Src-transformed profile is more diverse with enrichment in sites on metabolic enzymes and RNA and protein synthesis and processing machinery. Forty-three pTyr sites (32 proteins) are predicted as major biologically relevant Src targets on the basis of frequent identification in both cell populations. This select group, of particular interest as diagnostic biomarkers, includes well-established Src sites on signaling/adhesion/cytoskeletal proteins, but also uncharacterized sites of potential relevance to the transformed cell phenotype.